Sunday

March 29, 2015

March 29, 2015

Posted by **Pablo** on Sunday, November 26, 2006 at 6:35pm.

cos8t * sin2t

sin(a+b) = sin(a)cos(b) + cos(a)sin(b)

replacing by by -b and using that

cos(-b)= cos(b)

sin(-b)= -sin(b)

gives:

sin(a-b) = sin(a)cos(b) - cos(a)sin(b)

Add the two equations:

sin(a+b) + sin(a-b) = 2sin(a)cos(b)-->

sin(a)cos(b)= 1/2 [sin(a+b) + sin(a-b)]

who found trigonometry?

**Answer this Question**

**Related Questions**

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

algebra - Can someone please help me do this problem? That would be great! ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...

Math - Calculus - The identity below is significant because it relates 3 ...

Trig - Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < ...

Calculus 12th grade (double check my work please) - 1.)Find dy/dx when y= Ln (...

trig - The expression 4 sin x cos x is equivalent to which of the following? (...

math - Can you please check my work. A particle is moving with the given data. ...

math - Prove that for all real values of a, b, t (theta): (a * cos t + b * sin t...